Pre-exercise cryotherapy reduces myoglobin and creatine kinase levels after eccentric muscle stress in young women - Kusmierczyk, Justyna; Wiecek, Magdalena; Bawelski, Marek; Szygula, Zbigniew; Rafa-Zablocka, Katarzyna; Kantorowicz, Malgorzata; Szymura, Jadwiga (Frontiers in Physiology, 2024)
The aim of this study was to investigate the effect of pre-exercise whole-body cryotherapy (WBC) on muscle damage indicators following eccentric treadmill exercise in young women. Twenty-seven participants underwent two 1-hour downhill treadmill runs, replicating 60% of their maximal oxygen uptake, with a four-week intermission for recovery and treatment application. In this intermission, one group underwent 20 sessions of WBC, delivered five times a week at -120°C for 3 minutes each, while the comparison group received no such treatment. Markers of muscle injuryserum myoglobin concentration, creatine kinase and lactate dehydrogenase activity and also uric acid, and cell-free DNA (cfDNA) concentrationwere measured before and after downhill runs. The study observed a notable reduction in post-exercise myoglobin and CK levels in the WBC group after the second running session, suggesting that WBC can have a protective effects against muscle damage resulting from eccentric exercise.